Análisis fisicoquímico del agua en la vereda la lajita Tunja Según Resolución 2115 Del 2007. (2023)
Understanding the importance of water resources both for humans and for other living beings, this document is made, being of vital importance to know the state of the water that is being consumed by the rural community La Lajita, municipality of Tunja in the department of Boyacá , who do not have access to drinking water due to lack of economic resources, which prevents payment to the aqueduct provided in said neighborhood. Therefore, it is necessary to determine the quality of the water that is being consumed by the community of the village by carrying out a physicochemical analysis that allows obtaining the exact values of specific parameters such as: Acidity, alkalinity, turbidity, Color, hardness. , PH, conductivity, as well as a microbiological analysis of parameters in order to evaluate the presence of total and fecal coliforms and the presence of Escherichia coli in the body of water. Having these values, the comparison is made with resolution 2115 of 2007 issued by the Ministry of Social Protection, Ministry of Environment, Housing and Territorial Development. Therefore, after the analysis of results, it is finally concluded that the water resource is not suitable for human consumption, taking into account the physicochemical and microbiological parameters evaluated since factors such as: color and turbidity present high values compared to the resolution in question. Therefore, the possible uses that this resource could have and the alternatives for the community around this very important asset are defined.